2019
DOI: 10.3390/medicina55120786
|View full text |Cite
|
Sign up to set email alerts
|

Migraine without Aura and Subclinical Atherosclerosis in Young Females: Is Gut Microbiota to Blame?

Abstract: Background and Objectives: Migraine with aura (MA) could be considered a risk factor for developing atherosclerosis and cardio-vascular events. However, less is known about the relation between migraine without aura (MWA) and atherosclerosis. Our study aimed to assess whether young female migraineurs, with alterations of gut microbiota could associate early atherosclerosis. Materials and Methods: We conducted an exploratory cross-sectional, pilot study concerning 105 consecutive young females having MWA, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Over the past decades, gut microbiota dysbiosis has been increasingly associated with various conditions, either functional, such as irritable bowel syndrome [48,49] or organic such as atherosclerosis and hypertension [50][51][52] as well as metabolic syndrome and NAFLD [53,54]. There is growing support for the idea that gut microbiota dysbiosis could contribute to NAFLD development, with numerous pathways being engaged.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, gut microbiota dysbiosis has been increasingly associated with various conditions, either functional, such as irritable bowel syndrome [48,49] or organic such as atherosclerosis and hypertension [50][51][52] as well as metabolic syndrome and NAFLD [53,54]. There is growing support for the idea that gut microbiota dysbiosis could contribute to NAFLD development, with numerous pathways being engaged.…”
Section: Discussionmentioning
confidence: 99%
“…Georgescu et al observed a strong positive correlation between severity of migraine and dysbiosis assessed in fecal microbiota of IBS patients [ 156 ]. The same authors reported that about half of the population of young female migraineurs without aura had gut microbiota dysbiosis [ 157 ]. These authors concluded that patients with significant alterations in gut microbiota showed early signs of atherosclerosis and displayed severe migraine disability.…”
Section: Migraine and Functional Gi Disordersmentioning
confidence: 99%
“…Furthermore, elevated oxidative stress is involved in the pathophysiology of migraine (Cavestro, Ferrero, Mandrino, Di Tavi, & Rota, 2019; Ferroni et al, 2018). Interestingly, gut microbiota and permeability may be in association with the progression of migraine (G. Anderson, 2019; Georgescu et al, 2019). Herbal medicines discussed in the review have a significant impact on neurovascular processes of migraine, and therefore, hold bright prospects in the management of this disorder.…”
Section: Migraine Pathogenesismentioning
confidence: 99%